AB0841 TARGET OUTCOMES IN PsA: SIMULTANEOUS ACHIEVEMENT of ACR50-PASI100 AND BEYOND: INSIGHTS FROM SPIRIT-H2H AT WEEK 24. (13th June 2020) - Smolen, J. S.; Behrens, F.; Liu Leage, S.; Sapin, C.; De La Torre, I.; Meszaros, G.; Schett, G.; Gossec, L.; Ostor, A.; Combe, B.; Van den Bosch, F.
Abstract : Background: Psoriatic Arthritis (PsA) treatment should aim to achieve robust improvement of arthritis as well as control of extra-articular manifestations like the skin. SPIRIT-H2H evaluated the efficacy of ixekizumab (IXE) and adalimumab (ADA) in patients with active PsA and psoriasis, and naïve to biologic Disease-Modifying Anti-Rheumatic Drugs (bDMARDs). At week 24 (W24), IXE showed superiority to ADA in simultaneous achievement of ACR50 and PASI100 as well as significant improvement of treat-to-target and other extra-articular outcomes. Objectives: To examine and to compare PsA efficacy outcomes in patients beyond achievement of the primary endpoint of the SPIRIT-H2H trial at W24, irrespective of treatment allocation. Methods: All patients recruited had active PsA (defined as tender joint count ≥3/68, swollen joint count ≥3/66 and body surface area [BSA] ≥3%), and inadequate response to conventional synthetic (cs)-DMARDs. Patients were randomised 1:1 to open-label, assessor-blinded IXE or ADA. We conducted post-hoc analysis of SPIRIT-H2H (NCT03151551 ), categorizing patients into four independent groups based on the achievement of the primary outcome (ACR50 & PASI100), ACR50 only, PASI100 only or none of them after 24 weeks of treatment. Statistical analyses consisted of mixed model for repeated measurement and logistic regression models using non-response imputation. Results: At week 24, patients reaching simultaneously ACR50 and PASI100 had a statistically significant higher response in most treat-to-target endpoints than those meeting ACR50 only (p<0.05). In this latter group, a high response rate was observed in ACR70, MDA, DAPSA remission and PASI90 response (48.9%, 60.6%, 35.1%, 36.2%, respectively). In patients that did not achieve either ACR50 or PASI100, up to 1/3 of the patients did achieve ACR20, DAPSA score ≤14, or no physical impairment. Conclusion: Reflecting the complexity of PsA, different degrees of improvement were observed across all treat-to-target outcomes with greater improvements in patients that met ACR50 response regardless of skin resolution. These findings at week 24 need to be confirmed with a longer duration of treatment. Disclosure of Interests: Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene, Lilly and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai, Soyi Liu Leage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Christophe Sapin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Inmaculada De La Torre Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Gabriella Meszaros Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB, Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, Andrew Ostor Consultant of: MSD, Pfizer, Lilly, Abbvie, Novartis, Roche, Gilead and BMS, Speakers bureau: MSD, Pfizer, Lilly, Abbvie, Novartis, Roche, Gilead and BMS, Bernard Combe Grant/research support from: Novartis, Pfizer, Roche-Chugai, Consultant of: AbbVie; Gilead Sciences, Inc.; Janssen; Eli Lilly and Company; Pfizer; Roche-Chugai; Sanofi, Speakers bureau: Bristol-Myers Squibb; Gilead Sciences, Inc.; Eli Lilly and Company; Merck Sharp & Dohme; Pfizer; Roche-Chugai; UCB, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB